(untitled) (Intent Research Scientific Journal, 2023)
The integration of renewable energy sources into the grid presents numerous challenges, with intermittent generation being a major concern. Energy storage systems have emerged as a promising solution to mitigate the variability and uncertainty associated with renewable sources. This scientific paper presents a comprehensive study on enhancing energy storage solutions for renewable energy grid integration. The research examines the current state of energy storage technologies, their performance characteristics, and evaluates various methodologies to optimize their efficiency and cost-effectiveness. The study focuses on evaluating the benefits of different energy storage technologies in facilitating the seamless integration of renewable energy into the grid, ultimately contributing to a more sustainable and reliable energy future.